PENGEMBANGAN SISTEM INFORMASI PEMASARAN BUAH PINANG BERBASIS WEB UNTUK PETANI DAN PEDAGANG: Information Systems, MYSQL, Web-Based, Marketing Areca Nut, SDLC - Yulvianda, Renaldi; Sutoyo, Mochammad Arief Hermawan; Ismail, Muhammad; Anzari, Yandi (JURNAL AKADEMIKA, 2025)
The Betel nut is a plantation commodity with significant economic potential, particularly as an export product. However, marketing activities among farmers and traders still face obstacles, such as limited access to price information, less than optimal promotions, and a narrow distribution network. This study aims to design and develop a web-based betel nut marketing information system that can support the promotion and transaction process. The system development method used refers to the System Development Life Cycle (SDLC) model, namely the waterfall, starting from user needs analysis, system design, implementation, and testing. This system was created using the PHP programming language with a MySQL database, and is equipped with key features such as product data management, price recording, information publication and communication media between farmers and traders, as well as a payment gateway feature. Testing results using the black box testing approach showed that the system can function according to the design. With this information system, it is expected that betel nut marketing will be more structured, market access will be wider, and farmers and traders will obtain a more competitive selling price.